LRSAM1 E3 ubiquitin ligase promotes proteasomal clearance of E6-AP protein - Mishra R.; Joshi V.; Upadhyay A.; Amanullah A.; Dubey A.R.; Singh S.; Dubey V.K.; Poluri K.M.; Jana N.R.; Mishra A. (My University, 2025)
Numerous proteins participate and actively contribute to the various cellular mechanisms, where several of them are crucial for regular metabolism, including survival. Thus, to maintain optimal cellular physiology, cells govern protein quality control functions with the assistance of comprehensive actions of molecular chaperones, the ubiquitin-proteasome system, and autophagy. In the ubiquitin-proteasome pathway, few quality control E3 ubiquitin ligases actively participate against misfolded protein aggregation generated via stress conditions. But how these quality control E3s active expression levels returned to basal levels when cells achieved re-establishment of proteostasis is still poorly understood. Our current study demonstrated that LRSAM1 E3 ubiquitin ligase promotes the proteasomal degradation of quality control E3 ubiquitin ligase E6-AP. We have observed the co-localization and recruitment of LRSAM1 with E6-AP protein and noticed that LRSAM1 induces the endogenous turnover of E6-AP. Partial depletion of LRSAM1 elevates the levels of E6-AP and affects overall cell cycle regulatory proteins (p53 and p27) expression, including the rate of cellular proliferation. The current finding also provides an excellent opportunity to better understand the basis of the E6-AP associated pathomechanism of Angelman Syndrome disorder. Additionally, this study touches upon the novel potential molecular strategy to regulate the levels of one quality control E3 ubiquitin ligase with another E3 ubiquitin ligase and restore proteostasis and provide a possible therapeutic approach against abnormal protein aggregation diseases. © 2020 Elsevier Inc.